Ականավոր հայագետը (Հրաչյա Աճառյանի ծննդյան 140-ամյակի առթիվ) - Հրաչյա Բալոյան (ՀՀ ԳԱԱ հրատ.)
Выдающийся арменовед Рачья Ачарян родился 8 марта 1876 г. в Константинополе. Научное наследие, оставленное им, сосредоточено в 250 больших и малых трудах. Он изучил все сферы арменистики, основал некоторые ее отрасли – история армянского языка, армянская диалектология и т. д. The eminent Armenologist Hrachya Acharyan was born on March 8, 1876 in Constantinople. His legacy includes 250 works, big and small. He had explored all spheres of Armenian Studies and even initiated some of its branches, like History of the Armenian Language, Armenian Dialectology, etc.
Keywords: Biography; Auxiliary Sciences of History; Philology; Linguistics; Language and Literature; General Works; History of Scholarship; The Humanities